Comparative determination of the time-dependent accumulation of metal oxides in the landfill gas combustion chamber deposits using SEM-EDS, XRF and ICP OES - Sevimoğlu, Orhan; Somek, Ozge Osturk; Yildiz, Fikret (Elsevier, 2024)
Non-purified landfill gas (LFG) leads to the formation of complex deposits in combustion chambers due to impurities such as siloxanes, sulfur compounds, and organometallic compounds containing elements such as Si, S, Sb, Sn. This study focused on identifying the elemental composition of deposits from four combustion chambers using analytical techniques including SEM-EDS, WDXRF, and microwave digestion ICP OES. The dominant element, Si, with concentrations (wt%) in the deposits was measured by SEM-EDS, ICP-OES, and WDXRF, respectively, as follows: 17.04 +/- 8.59, 21.89 +/- 4.39, and 16.63 +/- 0.94 for cylinder head deposits, and 13.28 +/- 6.97, 15.40 +/- 5.40, and 12.64 +/- 1.64 for piston head deposits. Excluding C, O and N, which could not be analyzed by all three techniques, the multi-analytical approaches demonstrated strong correlations between EDS results and those obtained from WDXRF and ICP OES, with R-2 values of 0.9173 and 0.9002 for cylinder head deposits, respectively. It was also revealed that the elemental composition of deposits varied between combustion chambers. The average mass fractions of all deposit surfaces were ranked as follows for elements exceeding 1 %: O (45.38 %) > Si (16.67 %) > Ca (9.87 %) > Sb (7.21 %) > S (5.98 %) > Sn (3.51 %) > C (2.83 %) > P (2.35 %). Elements below 1 % were ranked as: Na (0.91 %) > N (0.80 %) > Al (0.74 %) > Fe (0.48 %) > Mg (0.30 %). Consequently, the multi-spectrometry analysis approach provides a more comprehensive understanding of the deposit composition, enabling the determination of primary contributors and the most elements. Future studies may involve more general determining the concentrations of organometallic compounds in the LFG, which are the source of the elements found in the deposit.
Keywords: Landfill gas; Elemental analysis; Deposit accumulation; Spectroscopy analysis